Polarization effects in optical fiber communication and distributed vibration sensing systems - Zhang, Ziyi (University of Ottawa (Canada), 2009)
This thesis includes studies of polarization effects in two main research areas of optical fiber technology: optical fiber communication systems and optical fiber sensors. Polarization of light in optical fiber is sensitive to environmental disturbances. On the negative side, this results in complex measurement processes and errors in communication systems caused by dynamic polarization mode dispersion (PMD) and polarization dependent loss (PDL). On the positive side though, it also results in the possibility of developing a distributed optical fiber vibration sensor. For the purpose of fast polarization measurement for high bit-rate communication systems, a new PDL vector method was proposed based on the equation of motion in Stokes space. It is capable of providing accurate PDL measurements while requiring less measurement steps compared with other available techniques. We had performed a PMD field test, and found the fastest PMD change in submarine fibers under the Caribbean Sea. With long measurement duration (>24h) on one pair of fiber, correlations between polarization effects and tides were reported for the first time. A histogram of the differential group delay (DGD) data and an auto-correlation function of state of polarization (SOP) and DGD were validated by theoretical fittings. The average and fastest drift time for both SOP and DGD was found to be ∼3min and less than 15s, respectively. Polarization effects were then utilized as a sensing parameter to detect and locate external disturbances along the optical fiber. A system based on polarization optical time domain reflectometry (Polarization-OTDR) technique was developed in order to pinpoint the disturbances as well as to give events' frequency information. For the first time, a fully distributed optical fiber vibration sensor has been demonstrated in a 1km fiber link with 10m spatial resolution and 5kHz maximum detectable frequency. Moreover, by our proposed spectrum analysis, multiple simultaneous events with the same frequency components can be identified.
Keywords: Physics, Optics.